Peranan Pendidikan Anti Korupsi Kepada Anak Dalam Membangun Generasi Anti Korupsi - Dela Safitri; Dewi Gita Pertiwi; Sakila Setia Wati (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Corruption is a significant obstacle to the progress of countries, especially in Indonesia, and has infiltrated almost every aspect of government affairs. This section explains how teaching children about honesty and fairness from a young age helps them avoid corruption. Using qualitative methods through interviews and records, this study seeks to understand how virtues such as honesty, responsibility, discipline, perseverance, and other ethical principles can be cultivated in education. Anti-corruption education teaches students about integrity and ethics. This section also points out some of the barriers to anti-corruption instruction, including narrow syllabi, little public awareness, and a permissive bribery environment. Therefore, a concerted and comprehensive effort is needed among educational institutions, family units, and government agencies to build an educational framework that serves as a strong foundation for eliminating corruption from the youth.